p63 and ZNF148 cooperate to regulate head and neck squamous cell carcinoma - Rosalba Pecorari; Mara Mancini; Artem Smirnov; Giacomo Corleone; Flavia Novelli; Anna Maria Lena; Mariacristina Franzese Canonico; Manuela Montanaro; Angela Cappello; Andrea Sacconi; Gabriella Misso; Michela Falco; et al. (Proceedings of the National Academy of Sciences, 2025)
Head and neck squamous cell carcinoma (HNSCC) is a common and aggressive malignancy. While significant advances have been made in the management of low-grade cancer, treatment of advanced HNSCC remains challenging. Here, we used a proteomic approach to find binding partners of the oncogene p63, the most frequently amplified transcription factor in HNSCC. We identified a zinc finger protein, ZNF148, which is coexpressed and physically binds p63 in carcinoma cells. Genome occupancy analyses identified a functional transcribed enhancer-derived RNA (eRNA) upstream of the CCND1 gene occupied by both factors. Mechanistically, p63 and ZNF148 control transcription of this eRNA, leading to overexpression of cyclin D1 to reinforce tumor cell proliferation. Importantly, this axis is specific for cancer cells and remains inactive in normal epithelial cells. The expression levels of these factors and the eRNA are positively correlated in cancer and associated with advanced stage and metastasis. Collectively, our data reveal a molecular pathway controlling HNSCC progression and identify potential selective targets for cancer treatment.